Hairy-root-inducing plasmid: physical map and homology to tumor-inducing plasmids. - Huffman, G A (1984)
A physical map was constructed for the 250-kilobase plasmid pRiA4b, which confers the virulence properties of a strain of Agrobacterium rhizogenes for hairy root disease in plants. The complete HindIII and KpnI restriction map was determined from a collection of overlapping HindIII partial digest clones. Homologous regions with two well-characterized plasmids that confer virulence for crown gall disease, plasmids pTiA6 and pTiT37, were mapped on pRiA4b. As much as 160 kilobases of pRiA4b had detectable homology to one or both of these crown-gall-tumor-inducing plasmids. About 33 kilobases of pRiA4b hybridized to the vir region of pTiA6, a segment of DNA required for virulence of Agrobacterium tumefaciens. Portions of pTiA6 and pTiT37 transferred into plant cells in crown gall disease (T-DNA), shared limited homology with scattered regions of pRiA4b. The tumor morphology loci tms-1 and tms-2 from the T-DNA of pTiA6 hybridized to pRiA4b. A T-DNA fragment containing the tml and tmr tumor morphology loci also hybridized to pRiA4b, but the homology has not been defined to a locus and is probably not specific to tmr. A segment of pRiA4b T-DNA which was transferred into plant cells in hairy root disease lacked detectable homology to pTiA6 and had limited homology at one end to the T-DNA of pTiT37.